2014
DOI: 10.1021/bi401260f
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole C-2 Hydrogen/Deuterium Exchange Reaction at Histidine for Probing Protein Structure and Function with Matrix-Assisted Laser Desorption Ionization Mass Spectrometry

Abstract: We present a mass spectrometric method for analyzing protein structure and function, based on the imidazole C-2 or histidine Cε1 hydrogen/deuterium (H/D) exchange reaction, which is intrinsically second order with respect to the concentrations of the imidazolium cation and OD− in D2O. The second-order rate constant (k2) of this reaction was calculated from the pH-dependency of the pseudo-first-order rate constant (kφ) obtained from the change of average mass ΔMr (0 ≤ ΔMr < 1) of a peptide fragment containing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…We also compared the susceptibility of each His residue (Dr) with the second-order rate constant k 2 of the H/D exchange reaction as another index of photo-oxidation, expecting that both of these parameters can have a positive correlation with the accessibility of each His residue to solvent 21 . Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also compared the susceptibility of each His residue (Dr) with the second-order rate constant k 2 of the H/D exchange reaction as another index of photo-oxidation, expecting that both of these parameters can have a positive correlation with the accessibility of each His residue to solvent 21 . Fig.…”
mentioning
confidence: 99%
“…The pK a value and the second-order rate constant k 2 of the hydrogen/deuterium (H/D) exchange reaction at the imidazole C2 (histidine C ε1 ) position of each His residue were measured by the mass spectrometric titration of pseudo-first-order rate constant ϕ k of the H/D-change reaction against pH as reported in our previous publications 6,17,21 . The D 2 O solutions of buffers used were 50 mM sodium acetate (pH 3.5-4.5), 50 mM MES (pH 5.0-7.0), and 50 mM HEPES (pH 7.5-9.5).…”
mentioning
confidence: 99%
“…In this case, when the p K a values are equal, the higher k max values for His 52 and His 80 compared to His 66 , His 69 , and His 84 must be due to differences in the local protein environment, for example, in solvent accessibility or hydrogen bonding patterns. 5,14 …”
Section: Resultsmentioning
confidence: 99%
“…Previously, the uptake has been derived either from the ratio of the monoisotopic (I) and I + 1 peak 4 or by calculating the average mass from the isotopic distribution, where the difference from the unexchanged average mass is used to quantify the uptake of deuterium. 14 The first method has the disadvantage that it cannot be used in the cases of peptides containing two or more histidines. We also found that using the average mass was susceptible to artifacts due to the lowest-intensity peaks’ being unreliably detected.…”
Section: Methodsmentioning
confidence: 99%
“…H/D exchanges at CE1 of the imidazole ring have been observed in histidine itself, in peptides and in proteins, and were utilized to estimate the pK a of the histidine residues. It has been suggested that the rate of exchange depends on the pH of the solution, solvent accessibility and the pK a of the histidine side chains (Bradbury et al, 1973;Hayashi et al, 2014). The exchange of the HE1 atom with DE1 has been reported for the neutron crystallographic analysis of myoglobin by Ostermann et al (2002).…”
Section: Figure 10mentioning
confidence: 93%